Analisis Penerapan Pembayaran Jasa Lingkungan Sektor Air pada Skala Daerah Aliran Sungai - Andi Setyo Pambudi (Jurnal Kebijakan Pemerintahan, 2025)
The degradation of the upstream area of the Cimanuk Watershed due to land conversion and deforestation has reduced the ecosystem’s capacity to regulate water availability and quality. This phenomenon highlights the urgency of applying economic instruments in water resource management, particularly through the implementation of Payment for Environmental Services (PES). However, a fair and measurable mechanism for determining the economic value of water at the watershed scale remains absent, weakening incentives for upstream conservation actors. This study aims to formulate a scientifically grounded water pricing mechanism as a tool to address market failure in valuing ecosystem services and to promote sustainable watershed governance. The research applies a mixed-method approach using three valuation techniques: Contingent Valuation Method (CVM), Value of Marginal Product (VMP), and Full Cost Pricing. Findings reveal a significant disparity between the downstream community’s willingness to pay (WTP) and the upstream community’s willingness to accept compensation (WTA), emphasizing the need to internalize environmental externalities into water pricing. Policy recommendations include the adoption of full cost pricing for water, integration of PES into watershed planning frameworks, and the establishment of a transparent and participatory mechanism for allocating conservation funds. Keywords: water pricing, environmental services, Cimanuk watershed, economic valuation